INVESTIGATION OF THE INFLUENCE OF POWER AND SPEED IN CO2 LASER ENGRAVING ON GLASS - Bluks, Artis; Rabkeviča, Kristīne; Vasaraudzis, Raivo; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
Laser technologies are a major priority in the development of our economy and society in the 21st century. One of the main applications of lasers is laser marking / engraving. The laser engraving method is widely used in many industries, including the glass industry. There are many ways to engrave glass, for example sandblasting, but it is time consuming, expensive and not as precise as laser engraving. The report contains glass engraving quality with CO2 laser, using different power and speed values.